1996
DOI: 10.1152/ajprenal.1996.271.1.f209
|View full text |Cite
|
Sign up to set email alerts
|

Role of reactive oxygen metabolites in DNA damage and cell death in chemical hypoxic injury to LLC-PK1 cells

Abstract: Hypoxia is considered to result in a necrotic form of cell injury. We have recently demonstrated a role of endonuclease activation, generally considered a feature of apoptosis, to be almost entirely responsible for DNA damage in hypoxic injury to renal tubular epithelial cells. The role of reactive oxygen metabolites in endonuclease-induced DNA damage and cell death in chemical hypoxic injury has not been previously examined. LLC-PK1 cells exposed to chemical hypoxia with antimycin A resulted in enhanced gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
57
1
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 0 publications
1
57
1
1
Order By: Relevance
“…Several lines of evidence suggest that plasmalogens, by virtue of their vinyl ether, act as antioxidants. The generation of ROS during chemical hypoxia has been well established [11,30,31]. Our ability to partly rescue cells with the antioxidant Trolox demonstrated that reactive oxygen generation had a role in the chemical hypoxia-induced cytotoxicity.…”
Section: Discussionmentioning
confidence: 75%
“…Several lines of evidence suggest that plasmalogens, by virtue of their vinyl ether, act as antioxidants. The generation of ROS during chemical hypoxia has been well established [11,30,31]. Our ability to partly rescue cells with the antioxidant Trolox demonstrated that reactive oxygen generation had a role in the chemical hypoxia-induced cytotoxicity.…”
Section: Discussionmentioning
confidence: 75%
“…ROS-induced cell death has been reported in a wide variety of cells, including renal tubular epithelial cells (RTE) (1,14,24,31,38,57,58) and nonrenal cells (25,40). Studies from other laboratories and that from ours have shown an important role of caspases in RTE injury (15, 21, 23, 33-36, 38, 41, 44, 46).…”
mentioning
confidence: 71%
“…The production of reactive oxygen species is a common phenomenon in plants under drought stress. These reactive oxygen species (ROS) generations led to lipid peroxidation (Sreeni-Nivasuhu et al 1999, Chen et al 2000, protein degradation (Jiang and Zhang 2001) and nucleic acid damages (Hagar et al 1996). To alleviate adverse effects of reactive oxygen species, plants have evolved an antioxidant defense system that include enzymes like superoxide dismutase, peroxidase and catalase etc.…”
mentioning
confidence: 99%